2010
DOI: 10.1186/1471-2458-10-158
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of stunting, overweight and obesity, and metabolic disease risk in rural South African children

Abstract: BackgroundLow- to middle-income countries are undergoing a health transition with non-communicable diseases contributing substantially to disease burden, despite persistence of undernutrition and infectious diseases. This study aimed to investigate the prevalence and patterns of stunting and overweight/obesity, and hence risk for metabolic disease, in a group of children and adolescents in rural South Africa.MethodsA cross-sectional growth survey was conducted involving 3511 children and adolescents 1-20 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
245
5
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(274 citation statements)
references
References 40 publications
19
245
5
5
Order By: Relevance
“…Regarding concurrent undernutrition and overnutrition in Vietnam, the prevalence we found is comparable to other low- and middle-income countries [11,12]. Between 1945 and 1975, Vietnam experienced a long period of food shortage due to war, which was followed by post-war consequences, resulting in a high prevalence of underweight and stunting.…”
Section: Discussionsupporting
confidence: 58%
“…Regarding concurrent undernutrition and overnutrition in Vietnam, the prevalence we found is comparable to other low- and middle-income countries [11,12]. Between 1945 and 1975, Vietnam experienced a long period of food shortage due to war, which was followed by post-war consequences, resulting in a high prevalence of underweight and stunting.…”
Section: Discussionsupporting
confidence: 58%
“…Compared with a cohort of healthy black South African children as published by Kimani-Murage et al, 12 patients with FA were found to be significantly underweight (weight for age z-score <−2) and stunted (height for age z-score <−2) for age ( Table 1).…”
Section: Resultsmentioning
confidence: 86%
“…Weight for age z-scores could only be calculated in children younger than the age of 10 years as the World Health Organization calculators do not allow for a calculation in those older than 10 years of age. The z-scores were used to compare the growth measurements of the study group with a cohort of healthy (cohort of rural South African children presumed not to have significant chronic illness or disease) black South African children as published by Kimani-Murage et al 12 The frequency of individuals with weight for age and height for age z-scores <−2 in the two groups was compared using Fisher's exact test. The frequency of each described physical phenotypic parameter was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Africa is at an early stage of epidemiological transition from communicable to chronic, non-communicable diseases (NCD) (Oladapo et. al., 2010;Kimani-Murage et. al., 2010).…”
Section: Introductionmentioning
confidence: 99%